Biologic effects of biosynthesized oroxylum indicum/silver nanoparticles on human periodontal ligament stem cells - Prapaipittayakhun, Jaruthai; Boonyuen, Supakorn; Zheng, Alvin Lim Teik; Apinyauppatham, Komsan; Arpornmaeklong, Premjit (Elsevier, 2022)
The biosynthesis of silver nanoparticles using plant extracts is a safe and efficient method. Human periodontal stem cells (hPDLSCs) can promote periodontal tissue formation for regenerative therapy. The current study aimed to biosynthesize silver nanoparticles (AgNPs) using stem bark extracts from Oroxylum indicum (L) Kurz (OI) as a reducing agent (OI/AgNPs) and investigate the biological properties of OI/AgNPs on human periodontal ligament stem cells (hPDLSCs). The OI/AgNPs were biosynthesized and characterized using UV“vis spectrophotometry (UV’vis), Fourier transform infrared spectroscopy (FTIR), X-ray diffraction (XRD), transmission electron microscopy (TEM) and zeta potential analyses. The hPDLSCs were stimulated with hydrogen peroxide (H2O2, H2O2-hPDLSCs) and bacterial lipopolysaccharide (LPS, LPS-hPDLSCs) and encapsulated in the hydrogel. After that, the levels of cell viability, interleukin-1beta (IL-1b), alkaline phosphatase (ALP) activity, and calcium content were measured and compared with quercetin (QT) as a reference flavonoid. The OI/AgNPs were stable spherical nanoparticles with a size range of 21.49 ± 0.32 nm, and biosynthesis enhanced the antioxidant and biological effects of the OI/AgNPs. The accumulation of OI/AgNPs in the cytoplasm of hPDLSCs with high levels of cell viability was demonstrated. OI/AgNPs increased the cell growth of H2O2-hPDLSCs and decreased the levels of IL-1b secretion from LPS-hPDLSCs. The OI/AgNPs increased the ALP activity and calcium content of the hPDLSCs. In conclusion, the biosynthesized OI/AgNPs were noncytotoxic and could protect hPDLSCs against oxidative stress and inflammatory stimuli and promote osteoblastic differentiation; thus, they are applicable for the regenerative treatment of peri‘implantitis.